2017
DOI: 10.14738/abr.52.2768
|View full text |Cite
|
Sign up to set email alerts
|

Country Culture and National Innovation

Abstract: Innovation, the implementation of creative ideas, is not only vital to growth but also to survival as companies and nations must innovate to compete in a rapidly changing global economy. Researchers are just beginning to understand the relationship between country culture and innovation. In a number of studies, cultural dimensions have correlated significantly with measures of innovation and creativity. However, it is difficult to compare findings across studies as multiple frameworks have been used to operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 4 publications
1
39
0
2
Order By: Relevance
“…Similarly, high individualism has been associated with higher levels of national innovation (e.g., Khan and Cox, 2017 ), implying that higher collectivism is related to lower levels of the same (but see Sarooghi et al, 2015 ). More collectivist cultures represent interdependent social structures, preferring a sense of community over individual needs, and putting others before themselves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, high individualism has been associated with higher levels of national innovation (e.g., Khan and Cox, 2017 ), implying that higher collectivism is related to lower levels of the same (but see Sarooghi et al, 2015 ). More collectivist cultures represent interdependent social structures, preferring a sense of community over individual needs, and putting others before themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Past literature has consistently noted the vital role played by culture in determining creativity and innovation ( Westwood and Low, 2003 ; Shah, 2013 ; Hermida et al, 2019 ). Khan and Cox (2017) suggested that societies displaying higher individualism and indulgence, and lower masculinity were associated with more innovation (as measured by the Global Innovation Index; GII). Along with individualism (which has been linked with the size of the creative industry, Rinne et al, 2013 ), femininity, long-term orientation, indulgence, and low uncertainty avoidance were found to be key in aiding innovation ( Prim et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, literature is almost unanimous in accepting the influence of national culture on innovative performance. There are several studies analysing the effect of Hofstede's cultural dimensions on the level of innovation performance in a specific country [ [45] , [46] , [47] ]. Recent studies have also examined the influence of national culture on core dimensions of responsible innovation, some of which directly related to co-creation: anticipation, reflexivity, deliberation, responsiveness and participation [ 24 , 38 ].…”
Section: A New Scenario For University-industry Collaborationmentioning
confidence: 99%
“…This influence, in turn, is determined by cultural dimensions at the moment of technology adoption (Kedia and Bhagat, 1988;Van Everdingen and Waarts, 2003). Societies with high levels of individualism, low power distance, low aversion to risk and indulgence present characteristics such as freedom, taste for risk, independence, adaptability, propensity to change, pursuit of objectives, assertiveness or importance of leisure that relate them positively with technological acceptance (Gales, 2008: Hofstede, 2011Kedia and Bhagat, 1988;Khan and Cox, 2017;Syed and Malik, 2014;Van Everdingen and Waarts, 2003). Collective, risk-averse and restrictive societies, with a high level of power distance, by contrast, are not prone to technological adoption as they are characterised by rigidity, hierarchy, respect for traditions, aversion to change or existence of strict norms (Hofstede, 2011;Hofstede and Bond, 1988;Steenkamp et al, 1999;Zmud, 1982).…”
Section: Culture and Technologymentioning
confidence: 99%
“…Cultures with a low power distance present values such as autonomy and lack of rigidity associated both with greater technological acceptance (Mumford and Licuanan, 2004) and high levels of CQ (Early and Ang, 2003;Templer et al, 2006). Indulgent societies observing values such as freedom, pursuit of leisure or entertainment (Hofstede, 2011) are associated with higher levels of technological acceptance (Khan and Cox, 2017;Syed and Malik, 2014) and share common characteristics of CQ such as freedom (Ang et al, 2007). The relationship between cultures with long-term or short-term orientation and technological acceptance is unclear (Table III).…”
Section: Culture and Technologymentioning
confidence: 99%